Post-Darwinian Kantians and Post-Kantian Darwinians: Epistemology, Metaphysics, and Science - Ramírez Jiménez, Adrián Josué (2025)
In this article, I argue that Kant's work influenced the epistemology and science of the 19th and 20th centuries. This influence can be understood in both positive and negative ways. To address this, I consider two paradigmatic cases. The first is Thomas Kuhn, who defined himself as a «post-Darwinian Kantian» in his text, The Road since Structure. Kuhn is interesting in addressing the question of the meaning of this statement. The second case is Ernst Haeckel, who begins by criticizing Kant's dualist philosophy. The influence here is negative if we consider his monistic approach.